Finally, an effort is under way to make Net searches easier - Livingston, Brian (InfoWorld, 1999)
Danny Sullivan, editor of Search Engine Watch, has announced the Search Engine Standards Project. Sullivan's goal is to bring together major search engine executives so that users need to learn only one set of search techniques, which will work across all engines.